Desenvolvimento de método espectrofotométrico para análise de paraformaldeído em saneantes comerciais e industriais - Fagnani, Enelton [UNESP]; Melios, Cristo Bladimiros [UNESP]; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (My University, 2002)
This paper describes a spectrophotometric method for the paraformaldehyde analysis in industrial and commercial disinfectant samples using chromotropic acid, concentrated hydrochloridric acid and hydrogen peroxide. The reaction produces a violet-red compound (λmax = 575 nm). The method permits the determination of paraformaldehyde over a concentration range of 0.8-4.8 mg L-1 and the results obtained by the proposed method compared very favorably with those obtained by NIOSH's standard procedure.
Development of spectrophotometric method for the analysis of paraformaldehyde in commercial and industrial disinfectants
Keywords: Chromotropic acid; Disinfectant analysis; Formaldehyde quantification; Spectrophotometry